Risk/caution of vitamin D insufficiency for quarantined athletes returning to play after COVID-19 - Saita, Y. (BMJ Open Sport & Exercise Medicine, 2020)
With the ongoing COVID-19 outbreak, athletes have been restricted from outdoor training. This has affected the nutritional status of athletes in various ways, especially with regard to their vitamin D status/level, which is produced in response to sun exposure. Vitamin D is essential for maintaining bone mass, muscle strength and physical performance. It likewise plays multiple other roles in the body, such as helping in calcium absorption and supporting the immune system. Therefore, sufficient vitamin D is indispensable not only for keeping healthy musculoskeletal conditions, but also for improving immune response, especially amidst the COVID-19 outbreak.